2014
DOI: 10.1371/journal.pone.0107104
|View full text |Cite
|
Sign up to set email alerts
|

Do Ask, Do Tell: High Levels of Acceptability by Patients of Routine Collection of Sexual Orientation and Gender Identity Data in Four Diverse American Community Health Centers

Abstract: BackgroundThe Institute of Medicine and The Joint Commission have recommended asking sexual orientation and gender identity (SOGI) questions in clinical settings and including such data in Electronic Health Records (EHRs). This is increasingly viewed as a critical step toward systematically documenting and addressing health disparities affecting lesbian, gay, bisexual, and transgender (LGBT) people. The U.S. government is currently considering whether to include SOGI data collection in the Stage 3 guidelines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
172
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(183 citation statements)
references
References 14 publications
9
172
0
2
Order By: Relevance
“…The capacity of the electronic health record to document gender identity should be analyzed and updated, and registration and appointment scheduling procedures revised to include questions inclusive of all gender identities. [35][36][37] Staff members who answer the phone should be trained to make no assumptions about gender identity from the timbre of a person's voice, the gender marker on their medical record, or their legal name.…”
Section: Recommendations For Providers On How To Conduct the Pelvic Exammentioning
confidence: 99%
“…The capacity of the electronic health record to document gender identity should be analyzed and updated, and registration and appointment scheduling procedures revised to include questions inclusive of all gender identities. [35][36][37] Staff members who answer the phone should be trained to make no assumptions about gender identity from the timbre of a person's voice, the gender marker on their medical record, or their legal name.…”
Section: Recommendations For Providers On How To Conduct the Pelvic Exammentioning
confidence: 99%
“…Recent research suggests that SGM individuals are more likely to disclose SOGI information if asked and are willing to disclose SOGI information if they know why they are being asked. 20,21 Several commentaries and opinion-based articles suggest that the collection of SOGI data can improve patient outcomes and patient-physician communication. [22][23][24] There was a misperception identified in this study, which has also been identified in previous research, that sexual orientation is only relevant if the issue at hand is directly related to sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Although finding inclusive and clinically useful language to denote patient SO/GI data in the EHR can be challenging, research demonstrates that heterosexual and LGBT individuals are overwhelmingly supportive of this information collection when respectfully asked and provided reasoning to why this information is clinically relevant [33]. Additionally, researchers with the Community Health Applied Research Network have determined that asking questions pertaining to SO/GI is an appropriate standard for health centers that are diverse in terms of geography, gender, region, race/ethnicity, sexual orientation and age [34].…”
Section: Challenges To Collecting So/gi Datamentioning
confidence: 99%